Reassembling Creation: Green Ethics and Scholarly Disciplines in the Islamic Tradition = āʾʿāda tškīl ālḫṭāb ālbīīʾī: ālāʾḫlāq ālḫḍrāʾ ūālḥqūl ālmʿrfīa fī āltrāṯ ālāʾslāmī - Krawietz, Birgit (Journal of Islamic ethics, 2025)
While the literature on Islamic Green Ethics (GE) has burgeoned, its discourses often remain constrained, either by mirroring global environmental narratives or by uncritically repeating doctrinal postulates. This editorial argues for a more robust and historically grounded approach, proposing a methodology of "reassembling creation" through a systematic engagement with the full spectrum of the Islamic tradition. It introduces a tripartite typology, distinguishing between scholarly disciplines, sub-disciplines, and specialised genres, as an analytical framework to map this vast intellectual landscape. This framework facilitates engaging with a diverse array of sources, including jurisprudence (fiqh), theology (kalām), philosophy (falsafa), Sufism (taṣawwuf), and practical genres like Prophetic medicine (ṭibb al-nabawī) and public supervision (ḥisba). The articles included in this thematic issue serve as case studies that embody this interdisciplinary and critical method. The contributions derive principles from the Qurʾān and Sunna, analyse classical philosophical traditions, and construct contemporary ethical frameworks from both Sunnī and Shīʿī perspectives. Ultimately, this editorial and the accompanying articles aim to stimulate a more comprehensive and critically engaged discourse, demonstrating the Islamic tradition’s rich potential to address contemporary ecological challenges.